SISTEM INFORMASI GEOGRAFIS PEMETAAN LOKASI ATM DAN AGEN LINK DI KOTA TEMBILAHAN - Saputra, Feri Adha; Abdullah; Jibril, Muhammad (JUTI UNISI, 2023)
In Indragiri Hilir Regency, there are many ATM locations at several points in the downtown area of Tembilahan and Link Agents spread throughout Indragiri Hilir Regency. However, not all people in Indragiri Hilir Regency know the location of ATMs and Link Agents, especially those that are far from the center of Tembilahan city and from other areas that have just set foot in the downstream Indragiri district. So the researchers tried to build a Web-based Geographic Information System, by mapping the locations of ATMs and Link Agents spread across Indragiri Hilir District. The purpose of this study is to design a web-based Geographic Information System application that can provide accurate data needed by users who need information. This study uses the Waterfall development model or "Linear Sequential Model" which describes a systematic and sequential approach to software development. At the analysis stage the researcher uses PIECES analysis. The goal is to minimize the weaknesses of the system that will be made. In the process of designing the system, researchers used modeling with the UML approach. The results of this research can provide instructions and make it easier for users to find the location of the nearest ATM and Link Agent in the city of Tembilahan because the system created has already been equipped with location points and the route the user wants to go.